2017
DOI: 10.12669/pjms.333.12345
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ramadan specific diabetes education (RSDE); A prospective study

Abstract: Objective:To observe the role of Ramadan Specific Diabetes Education (RSDE) in the management of fasting patients with diabetes.Methods:This prospective study was carried out at out-patients department (OPD) of Baqai Institute of Diabetology & Endocrinology (BIDE), in 2012. Recruitment of patients started a month prior to Ramadan. Muslim patients with diabetes whether had their first or on follow up visit to the OPD and showed intention to hold fast in the month of Ramadan, were included. A printed broacher fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…It shows that the impact of the 24-hours helpline service and pre-Ramadan education was similar to a previous study for people with diabetes [9]. In Ahmedani MY et al's study, patients with pre-Ramadan diabetes education also showed significantly better results for Ramadan-specific diabetes management recommendations as compared to patients without diabetes education [15].…”
Section: Figure 4: Frequency Of Calls On the Basis Of The Type Of Diasupporting
confidence: 81%
“…It shows that the impact of the 24-hours helpline service and pre-Ramadan education was similar to a previous study for people with diabetes [9]. In Ahmedani MY et al's study, patients with pre-Ramadan diabetes education also showed significantly better results for Ramadan-specific diabetes management recommendations as compared to patients without diabetes education [15].…”
Section: Figure 4: Frequency Of Calls On the Basis Of The Type Of Diasupporting
confidence: 81%
“…However, recent studies have shown that the newer anti-diabetic medications – DPP-4 inhibitors, GLP-1 agonists, and SGLT2 inhibitors – are safe during Ramadan fasting and have lower risk for hypoglycaemia compared to SU [12,14,18,19]. Pre-Ramadan individualized advice and education provided at our centre may have played a role in preventing significant increase in the rate of hypoglycaemia [20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, the Ramadan Specific Diabetes Education (RSDE) study found that patients who received this type of education tended to engage in safer fasting practices when compared to those who did not receive this type of education. 22 These programs were also able to reduce the development of diabetes-related complications that was observed while patients fasted during the EPIDIAR study [7]. Also evident was the fact that structured educational and interventional programs are important for diabetic patients.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the Ramadan Specific Diabetes Education (RSDE) study found that patients who received this type of education tended to engage in safer fasting practices when compared to those who did not receive this type of education. 22…”
Section: Discussionmentioning
confidence: 99%